Efficacy of 1, 550-nm Erbium-Glass Fractional Laser Treatment and Its Effect on the Expression of Insulin-Like Growth Factor 1 and Wnt/β-Catenin in Androgenetic Alopecia. Issue 10 (October 2018) - Meephansan, Jitlada; Ungpraphakorn, Nawaporn; Ponnikorn, Saranyoo; Suchonwanit, Poonkiat; Poovorawan, Yong
Abstract : BACKGROUND: A new treatment for androgenetic alopecia (AGA) is a 1, 550-nm erbium-glass (Er:Glass) fractional laser. The wound healing process associated with this treatment is believed to be due to the stimulation of hair regrowth. Both the Wingless-related integration site (Wnt) proteins and insulin-like growth factor 1 (IGF-1) are important molecules that promote new hair growth. OBJECTIVE: The aim of this study was to evaluate the efficacy of 1, 550-nm Er:Glass fractional laser treatment and determine the gene expression of IGF-1 and Wnt/β-catenin in patients with AGA. METHODS: Twenty-three patients with AGA were enrolled. They received 12 treatments at 2-week intervals. A scalp biopsy was performed to evaluate mRNA levels of Wnt10A and IGF-1. Histopathologic samples were collected. RESULTS: Significant increases in hair count and shaft diameter that occurred from Month 4 until the end of the study were observed. Histological results showed increases in the follicular unit, anagen hair count, and the anagen:telogen ratio. No up-regulation of Wnt10A and IGF-1 mRNA was observed. CONCLUSION: The 1, 550-nm Er:Glass fractional laser treatment can increase hair density and shaft diameter in patients with AGA. The mechanisms by which 1, 550-nm Er:Glass laser treatment induces new hair growth may not be limited to Wnt10A/β-catenin or IGF-1 expression.